Para-aramid diaphragm and preparation method thereof

By placing the substrate coated with aramid nanofiber dispersion in a mass consumer body and immersing it in a proton solution for replacement, heating and drying, the problems of para-aramid difficulty in dissolving and high melting point were solved, and a para-aramid separator with high porosity and excellent mechanical properties were prepared, which significantly improved the safety and electrochemical performance of lithium batteries.

CN119764747AActive Publication Date: 2025-04-04INST OF LASER MFG HENAN ACAD OF SCI

Patent Information

Application Number
CN202411974084.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

In the prior art, para-aramid is difficult to dissolve and has a high melting point, making it difficult to prepare a separator with high porosity. The commercial polyolefin separator has low mechanical strength and is not resistant to high temperatures, which can easily lead to short circuits and fires of lithium batteries.

Method used

By placing the substrate coated with the aramid nanofiber dispersion liquid in a proton donor, an aramid nanofiber gel is formed with a proton donor dispersed, and immersed it in the proton solution for replacement of solute and mass consumption body, heat and dry it to fix the separator structure, and obtain a para-aramid separator with high porosity.

Benefits of technology

The high porosity preparation of para-aramid separators is achieved, which improves the safety and electrochemical performance of lithium batteries, has higher mechanical strength and thermal stability, and can effectively prevent short circuits and fires of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764747A_ABST
    Figure CN119764747A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a para-aramid diaphragm and a preparation method thereof. The preparation method of the para-aramid diaphragm comprises the following steps: placing a substrate coated with an aramid nanofiber dispersion liquid in a proton donor to obtain aramid nanofiber gel dispersed with the proton donor; immersing the aramid nanofiber gel dispersed with the proton donor into a proton solution, and after a solute in the proton solution is replaced with the proton donor, heating and drying to obtain the para-aramid diaphragm; wherein the solute comprises low-decomposition-temperature / low-boiling-point salt and / or organic matter. The para-aramid diaphragm prepared by the preparation method of the para-aramid diaphragm has high porosity, tensile strength and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a para-aramid diaphragm and a preparation method thereof. Background Art

[0002] Lithium batteries have been widely used in new energy vehicles, smart phones, wearable devices, power station energy storage and other fields, but safety accidents such as fires and explosions related to lithium batteries occur frequently, causing social concerns about the safety of lithium batteries.

[0003] The separator is the core component to ensure the safety of lithium batteries. It plays the role of isolating the positive and negative electrodes and preventing short circuits. However, existing commercial polyolefin separators have low mechanical strength and are not resistant to high temperatures. They are easily pierced by lithium dendrites and easily shrink at high temperatures, causing internal short circuits in lithium batteries and even fire and explosion. Commercial polyolefin separators are difficult to ensure the safety of lithium batteries.

[0004] Para-aramid has excellent mechanical properties, excellent thermal stability and good flame retardancy, and is an ideal diaphragm material. The para-aramid diaphragm prepared with it is expected to significantly improve the safety of lithium batteries. However, the strong hydrogen bond network and high crystallinity make para-aramid difficult to dissolve (only soluble in concentrated sulfuric acid), have a high melting point (>400 °C), and are difficult to shape, making it difficult to prepare a diaphragm with high porosity. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a para-aramid diaphragm, so as to solve the problem in the prior art that it is difficult to prepare a diaphragm with high porosity due to the difficulty in dissolving para-aramid and the high melting point.

[0006] The present invention also provides a para-aramid diaphragm to solve the problem in the prior art that the diaphragm is difficult to ensure the safety of lithium batteries.

[0007] In order to solve the above problems, the present invention proposes a method for preparing a para-aramid diaphragm, and the technical solution adopted is: A method for preparing a para-aramid membrane comprises the following steps: placing a substrate coated with an aramid nanofiber dispersion in a proton donor to obtain an aramid nanofiber gel dispersed with the proton donor; immersing the aramid nanofiber gel dispersed with the proton donor in a proton solution, replacing the solute in the proton solution with the proton donor, and heating and drying to obtain the para-aramid membrane; wherein the solute comprises a salt with a low decomposition temperature / low boiling point, and / or an organic matter.

[0008] The beneficial effects of the present invention are: 1) The present invention immerses aramid nanofiber gel dispersed with proton donors into a proton solution to replace the solute in the proton solution with the proton donor, and fixes the diaphragm structure and reduces the shrinkage of the diaphragm and the collapse of the pore structure through heating and drying, thereby obtaining a para-aramid diaphragm with high porosity; 2) The present invention can adjust the pore size, porosity and other structures of the para-aramid membrane by adjusting the type and concentration of the proton donor and the type and concentration of the proton solution, thereby obtaining a para-aramid membrane with adjustable pore structure, and further adjusting the mechanical strength, rate and other properties of the para-aramid membrane; 3) Compared with aramid micron fibers, the aramid nanofibers used in the present invention have higher mechanical strength and specific surface area, and have a smaller and more uniform pore structure after forming, which can improve the safety and electrochemical performance of lithium batteries; 4) The preparation method of the present invention is compatible with existing industrial processing equipment and has the potential for large-scale application. It can realize its large-scale and efficient preparation and promote its practical application to improve the safety of lithium batteries.

[0009] In order to obtain a high-porosity aramid nanofiber gel dispersed with a proton donor, preferably, the proton donor is a proton solvent or the vapor of a proton solvent, and the proton solvent includes at least one of water, ethanol, methanol, ethylene glycol, glycerol, propanol, isopropanol, and butanol.

[0010] In order to effectively replace the solute in the proton solution with the proton donor, preferably, the low decomposition temperature / low boiling point salt includes at least one of carbonate, bicarbonate, ammonium salt, and nitrate; the organic matter includes oxalic acid; and the mass concentration of the solute in the proton solution is 0.5~20%.

[0011] More preferably, the ammonium salt is ammonium carbonate.

[0012] In order to fully replace the solute in the proton solution with the proton donor, preferably, the replacement time is 2 to 72 hours.

[0013] Preferably, the heating and drying comprises a first step of heating and a second step of heating, wherein the first step of heating is at a temperature of 30 to 120 °C for a time of 0.5 to 12 h; and the second step of heating is at a temperature of 100 to 200 °C for a time of 0.5 to 12 h. The present invention heats and dries the para-aramid membrane using two steps of heating, wherein the first step of heating removes the proton donor and the solvent in the proton solution, fixes the membrane structure, reduces the shrinkage of the membrane and the collapse of the pore structure during the second step of heating, and the second step of heating removes the solute in the proton solution and increases the porosity of the para-aramid membrane.

[0014] In order to make the aramid nanofiber gel dispersed with proton donors have a smaller and more uniform pore structure after being formed, preferably, the mass concentration of the aramid nanofiber dispersion is 0.5-2%.

[0015] In order to obtain an aramid nanofiber dispersion, preferably, the preparation method of the aramid nanofiber dispersion comprises the following steps: placing aramid micron fibers in an alkaline solvent system and stirring to obtain an aramid nanofiber dispersion. The present invention uses an alkaline solvent system to weaken the hydrogen bonding between aramid molecules at room temperature and pressure, thereby nano-forming the aramid fibers, with mild conditions and high efficiency.

[0016] In order to improve the efficiency of aramid fiber nano-forming, preferably, the alkaline solvent system includes an alkaline solvent system solute and an alkaline solvent system solvent, the alkaline solvent system solute includes at least one of potassium tert-butoxide, potassium hydroxide, sodium tert-butoxide, and sodium hydroxide; the alkaline solvent system solvent includes at least one of dimethyl sulfoxide, dimethylformamide, dimethylacetamide, tetrahydrofuran, acetone, toluene, xylene, benzene, and dichloromethane.

[0017] In order to further improve the efficiency of aramid fiber nano-fiberization, preferably, the mass ratio of the aramid micron fiber, the alkaline solvent system solute, and the alkaline solvent system solvent is 1: (0.5-1.5): (50-200).

[0018] The present invention also proposes a para-aramid diaphragm, and the technical solution adopted is: A para-aramid diaphragm is prepared by the above-mentioned method for preparing the para-aramid diaphragm.

[0019] The beneficial effects of the present invention are as follows: the para-aramid membrane of the present invention is a para-aramid membrane with adjustable pore structure, has high porosity, mechanical strength, thermal stability and rate performance, and can improve the safety and electrochemical performance of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the para-aramid membrane prepared in Example 1 of the method for preparing a para-aramid membrane of the present invention.

[0021] Figure 2 This is a SEM image of the para-aramid membrane prepared in Example 2 of the method for preparing a para-aramid membrane of the present invention.

[0022] Figure 3 This is a SEM image of the para-aramid membrane prepared in Example 3 of the method for preparing a para-aramid membrane of the present invention.

[0023] Figure 4 This is a SEM image of the para-aramid membrane prepared in Example 3 of the method for preparing a para-aramid membrane of the present invention. DETAILED DESCRIPTION

[0024] In the prior art, it is difficult to prepare a diaphragm with high porosity due to the difficulty of dissolving para-aramid and its high melting point. The present invention provides a method for preparing a para-aramid diaphragm, comprising the following steps: placing a substrate coated with an aramid nanofiber dispersion in a proton donor to obtain an aramid nanofiber gel dispersed with a proton donor; immersing the aramid nanofiber gel dispersed with a proton donor in a proton solution, replacing the solute in the proton solution with the proton donor, and heating and drying to obtain a para-aramid diaphragm; wherein the solute includes a salt with a low decomposition temperature / low boiling point, and / or an organic matter.

[0025] The technical concept of the present invention is as follows: the aramid nanofiber has higher mechanical strength and specific surface area, and has a smaller and more uniform pore structure after being formed, which can improve the safety and electrochemical performance of the lithium battery; a substrate coated with the aramid nanofiber dispersion is placed in a proton donor to obtain an aramid nanofiber gel dispersed with the proton donor, and the proton donor forms a dispersed pore structure in the aramid nanofiber gel; the aramid nanofiber gel dispersed with the proton donor is immersed in a proton solution to replace the solute in the proton solution with the proton donor, that is, the proton donor in the aramid nanofiber gel is replaced by the solute to obtain an aramid nanofiber gel dispersed with a pore structure, and the pore structure is filled with the solute; the aramid nanofiber gel dispersed with the pore structure is dried and heated to remove the proton donor and the proton solution, so as to achieve the fixation of the diaphragm structure and the stability of the pore structure, thereby obtaining a para-aramid diaphragm with an adjustable pore structure, which has high porosity, mechanical strength, thermal stability and rate performance, and can improve the safety and electrochemical performance of the lithium battery.

[0026] Specifically, the preparation method of the para-aramid diaphragm comprises the following steps: Firstly, para-aramid and alkaline solvent system solute are added into alkaline solvent system solvent, and stirred at 600-1500 rpm for 3-48 h to obtain an aramid nanofiber dispersion with a mass concentration of 0.5-2%; wherein the mass ratio of para-aramid, alkaline solvent system solute and alkaline solvent system solvent is 1: (0.5-1.5): (50-200).

[0027] Secondly, the aramid nanofiber dispersion is coated on a substrate, and then placed in a proton donor for 0.5 to 72 hours to obtain an aramid nanofiber gel dispersed with a proton donor; wherein the proton donor is a proton solvent or a vapor of a proton solvent, and the proton solvent includes at least one of water, ethanol, methanol, ethylene glycol, glycerol, propanol, isopropanol, and butanol; Next, the aramid nanofiber gel dispersed with proton donors is immersed in a proton solution for 2 to 72 hours, so that the solute in the proton solution fully replaces the proton donor in the aramid nanofiber gel to obtain the replaced aramid nanofiber gel; wherein the mass concentration of the solute in the proton solution is 0.5 to 20%; and the solvent in the proton solution includes at least one of water, ethanol, methanol, ethylene glycol, glycerol, propanol, isopropanol, and butanol; Finally, the replaced aramid nanofiber gel is first heated to 30~120 °C and maintained for 0.5~12 h to remove the proton donor and the solvent in the proton solution, and then heated to 100~200 °C and maintained for 0.5~12 h to remove the solute in the proton solution, finally obtaining a para-aramid membrane.

[0028] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. However, it will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. It should also be noted that, for ease of description, only the parts related to the invention are shown in the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below. It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0029] In the following embodiments, the para-aramid used is aramid short-cut fibers, the length of the short-cut fibers is 5 mm, and the raw materials used are common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.

[0030] 1. Specific embodiment of the method for preparing the para-aramid diaphragm of the present invention Example 1 The method for preparing the para-aramid diaphragm provided in this embodiment comprises the following steps: First, 2 g of para-aramid and 1.5 g of potassium tert-butoxide were added to 100 g of dimethyl sulfoxide and stirred at 1500 rpm for 3 h to obtain an aramid nanofiber dispersion with a mass concentration of 2%. Secondly, the aramid nanofiber dispersion is coated on a substrate and then placed in ethanol for 0.5 h to obtain an aramid nanofiber gel dispersed with ethanol; Next, the aramid nanofiber gel dispersed with ethanol was immersed in a proton solution for 2 h, wherein the solute in the proton solution was oxalic acid with a mass concentration of 4%, and the solvent was ethanol, so that the oxalic acid fully replaced the ethanol in the aramid nanofiber gel to obtain the replaced aramid nanofiber gel; Finally, the replaced aramid nanofiber gel was first heated to 120 °C and maintained for 0.5 h to remove ethanol, and then heated to 200 °C and maintained for 6 h to remove oxalic acid, finally obtaining the para-aramid membrane.

[0031] Example 2 The method for preparing the para-aramid diaphragm provided in this embodiment comprises the following steps: First, 2 g of para-aramid and 1.5 g of potassium hydroxide were added to 100 g of dimethyl sulfoxide and stirred at 100 rpm for 48 h to obtain an aramid nanofiber dispersion with a mass concentration of 0.5%. Secondly, the aramid nanofiber dispersion was coated onto a substrate and then placed in methanol for 72 h to obtain an aramid nanofiber gel dispersed with methanol; Next, the aramid nanofiber gel dispersed with methanol was immersed in a proton solution for 72 h, wherein the solute in the proton solution was ammonium carbonate with a mass concentration of 6%, and the solvent was an aqueous solution, so that the ammonium carbonate fully replaced the methanol in the aramid nanofiber gel to obtain the replaced aramid nanofiber gel; Finally, the replaced aramid nanofiber gel was first heated to 100 °C and maintained for 5 h to remove methanol and aqueous solution, and then heated to 170 °C and maintained for 0.5 h to remove ammonium carbonate, finally obtaining the para-aramid membrane.

[0032] Example 3 The method for preparing the para-aramid diaphragm provided in this embodiment comprises the following steps: First, 2 g of para-aramid and 3 g of sodium tert-butoxide were added to 200 g of dimethyl sulfoxide and stirred at 1000 rpm for 6 h to obtain an aramid nanofiber dispersion with a mass concentration of 1%. Secondly, the aramid nanofiber dispersion was coated onto a substrate and then placed in methanol vapor for 12 h to obtain an aramid nanofiber gel dispersed with methanol; Next, the aramid nanofiber gel dispersed with methanol was immersed in a proton solution for 24 h, wherein the solute in the proton solution was oxalic acid with a mass concentration of 4%, and the solvent was methanol, so that the oxalic acid fully replaced the methanol in the aramid nanofiber gel to obtain the replaced aramid nanofiber gel; Finally, the replaced aramid nanofiber gel was first heated to 30 °C and maintained for 12 h to remove methanol, and then heated to 100 °C and maintained for 12 h to remove oxalic acid, finally obtaining the para-aramid membrane.

[0033] Example 4 The method for preparing the para-aramid diaphragm provided in this embodiment comprises the following steps: First, 2 g of para-aramid and 3 g of sodium hydroxide were added to 200 g of dimethyl sulfoxide and stirred at 600 rpm for 8 h to obtain an aramid nanofiber dispersion with a mass concentration of 1%. Secondly, the aramid nanofiber dispersion is coated on a substrate, and then placed in a solution of ethanol and water in a mass ratio of 1:1 for 24 h to obtain an aramid nanofiber gel dispersed with ethanol and water; Next, the aramid nanofiber gel dispersed with ethanol and water was immersed in a proton solution for 24 h, wherein the solute in the proton solution was oxalic acid with a mass concentration of 6%, and the solvent was an aqueous solution, so that the oxalic acid fully replaced the ethanol and water in the aramid nanofiber gel to obtain the replaced aramid nanofiber gel; Finally, the replaced aramid nanofiber gel was first heated to 80 °C and maintained for 3 h to remove ethanol and water, and then heated to 150 °C and maintained for 6 h to remove oxalic acid, finally obtaining the para-aramid membrane.

[0034] In the present application, when the protic solvent includes at least one of ethylene glycol, glycerol, propanol, isopropanol, and butanol, the technical effect obtained is the same as the technical effect of the above embodiment.

[0035] In the present application, when the salt with low decomposition temperature / low boiling point includes at least one of carbonate, bicarbonate, and nitrate, the technical effect obtained is the same as the technical effect of the above embodiment.

[0036] In the present application, when the mass concentration of the solute in the proton solution is 0.5% and 20%, the technical effect obtained is the same as the technical effect of the above embodiment.

[0037] In the present application, when the alkaline solvent system solvent includes at least one of dimethylformamide, dimethylacetamide, tetrahydrofuran, acetone, toluene, xylene, benzene, and dichloromethane, the technical effect obtained is the same as the technical effect of the above embodiment.

[0038] 2. Experimental Examples Experimental Example 1 The surface morphology of the para-aramid diaphragms prepared in the above examples 1-4 was tested. Specifically, a scanning electron microscope was used to characterize the microscopic morphology of the samples at an acceleration voltage of 10 kV. The test results are as follows: Figure 1 , Figure 2 , Figure 3 and Figure 4 shown.

[0039] It can be seen that in the SEM images of the para-aramid membranes prepared in Examples 1-4, a small and evenly distributed pore structure is present, indicating that the para-aramid membrane prepared by the para-aramid membrane preparation method of the present application has a high porosity; and under different process conditions, para-aramid membranes with different pore structures can be obtained.

[0040] Experimental Example 2 The para-aramid diaphragms prepared in the above Examples 1-4 were tested for tensile strength, thermal shrinkage and rate performance. Specifically, for tensile strength, an electronic universal testing machine was used to test the tensile strength of the sample, with a tensile speed of 1 mm / min and an initial spacing of 10 cm. For thermal shrinkage temperature, the samples were heated at 100, 120, 140, 160, 180, 200, 220 and 240 °C for 1 h, respectively, and the shrinkage degree of the sample was measured. The lowest temperature at which the sample shrank by more than 10% was defined as the thermal shrinkage temperature of the sample. For rate performance, the sample was used to assemble a battery with lithium iron phosphate as the positive electrode and lithium sheet as the negative electrode, and the discharge capacity of the sample at 1C and 3C was tested by the battery testing system. The specific results are shown in Table 1: Table 1 Performance comparison of para-aramid diaphragms prepared in Examples 1-4 and commercial polyolefin diaphragms

[0041] It can be seen from Table 1 that the tensile strength of the para-aramid diaphragm prepared in Examples 1-4 is above 101 MPa, with a maximum of 135 MPa, which is much higher than the tensile strength of 15 MPa of the commercial polyolefin diaphragm; the heat shrinkage temperature of the para-aramid diaphragm prepared in Examples 1-4 is 240 °C, which is much higher than the heat shrinkage temperature of 120 °C of the commercial polyolefin diaphragm; the discharge capacity of the battery corresponding to the para-aramid diaphragm prepared in Examples 1-4 at 1C and 3C is 122 mAh g -1 and 80 mAh g -1 Above, up to 134 mAh g -1 and 108mAh g -1 , which is higher than the discharge capacity of 122 mAh g at 1C and 3C for the battery using commercial polyolefin separators. -1 and 77 mAh g -1 .

[0042] This shows that the para-aramid diaphragm prepared by the preparation method of the para-aramid diaphragm provided in the present application has a high porosity, and its tensile strength and thermal stability are far superior to those of commercial polyolefin diaphragms, thereby effectively ensuring the safety of lithium batteries. At the same time, the discharge capacity of the para-aramid diaphragm at 1C and 3C is significantly higher than that of the commercial polyolefin diaphragm, which can improve the electrochemical performance of lithium batteries.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a para-aramid diaphragm, characterized in that: The method comprises the following steps: placing a substrate coated with an aramid nanofiber dispersion in a proton donor to obtain an aramid nanofiber gel dispersed with the proton donor; immersing the aramid nanofiber gel dispersed with the proton donor in a proton solution, replacing the solute in the proton solution with the proton donor, heating and drying to obtain a para-aramid diaphragm; wherein the solute comprises a salt with a low decomposition temperature / low boiling point, and / or an organic matter.

2. The method for preparing a para-aramid diaphragm according to claim 1, characterized in that: The proton donor is a proton solvent or the steam of a proton solvent, and the proton solvent includes at least one of water, ethanol, methanol, ethylene glycol, glycerol, propanol, isopropanol, and butanol.

3. The method for preparing a para-aramid diaphragm according to claim 1, characterized in that: The low decomposition temperature / low boiling point salt includes at least one of carbonate, bicarbonate, ammonium salt and nitrate; the organic matter includes oxalic acid; and the mass concentration of the solute in the proton solution is 0.5-20%.

4. The method for preparing a para-aramid diaphragm according to claim 1, characterized in that: The replacement time is 2 to 72 hours.

5. The method for preparing a para-aramid diaphragm according to claim 1, characterized in that: The heating drying includes a first step of heating and a second step of heating, wherein the first step of heating is performed at a temperature of 30 to 120°C for a time of 0.5 to 12 h; and the second step of heating is performed at a temperature of 100 to 200°C for a time of 0.5 to 12 h.

6. The method for preparing a para-aramid diaphragm according to claim 1, characterized in that: The mass concentration of the aramid nanofiber dispersion is 0.5-2%.

7. The method for preparing a para-aramid diaphragm according to claim 6, characterized in that: The method for preparing the aramid nanofiber dispersion comprises the following steps: placing aramid micron fibers in an alkaline solvent system and stirring the system to obtain the aramid nanofiber dispersion.

8. The method for preparing a para-aramid diaphragm according to claim 7, characterized in that: The alkaline solvent system comprises an alkaline solvent system solute and an alkaline solvent system solvent, wherein the alkaline solvent system solute comprises at least one of potassium tert-butoxide, potassium hydroxide, sodium tert-butoxide, and sodium hydroxide; and the alkaline solvent system solvent comprises at least one of dimethyl sulfoxide, dimethylformamide, dimethylacetamide, tetrahydrofuran, acetone, toluene, xylene, benzene, and dichloromethane.

9. The method for preparing a para-aramid diaphragm according to claim 8, characterized in that: The mass ratio of the aramid micron fiber, the alkaline solvent system solute, and the alkaline solvent system solvent is 1: (0.5-1.5): (50-200).

10. A para-aramid diaphragm, characterized in that: The diaphragm is prepared by the method for preparing the para-aramid diaphragm according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance bulk aramid nanofiber aerogel as well as preparation method and application thereof

    CN112980044A

  • Preparation method of aramid nanofiber-based battery diaphragm with micro-nano porous structure regulated and controlled by pore-foaming agent

    CN113506950A

  • Porous titanium dioxide material as well as preparation method and application thereof

    CN115465888A

  • Preparation method of low-cost inorganic silicon-based aerogel

    CN116375042A

  • Preparation method of black phosphorus-loaded aramid nanofiber aerogel electromagnetic shielding material

    CN118994714A

Cited By

  • Preparation method of high-strength low-breathability para-aramid base film

    CN121123564A